Dual Sensory Impairment among Community Dwelling Rural Elderly: Concern for Rehabilitation. (29th January 2014) - Ramamurthy, Deepthi; Kasthuri, Arvind; Sonavane, Rekha
Abstract : Background. There is an increase in dual sensory impairment (DSI) (hearing and visual) with increase in elderly population. Most causes of DSI among elderly are treatable. This study determines the prevalence and characteristics of dual sensory impairment among elderly of a rural community. Material and Methods. A cross-sectional study conducted among 175 rural elderly. Visual acuity for distant vision was measured using Snellen E chart. Hearing ability was measured using pure tone audiometry. Results. The prevalence of hearing impairment was 72% and that of visual impairment was 48%. The overall prevalence of DSI among the study subjects was 17.7% and 32.6% depending on whether traditional pure tone average or high-frequency pure tone average was used to define moderate or worse degree of hearing impairment. DSI prevalence increased significantly with increase in age. DSI was higher among widow/ers and illiterates, who did not have any source of income and those who were financially dependent on others compared to their counter groups. Conclusion. Prevalence of DSI is high among community dwelling rural Indian elderly. Individuals with DSI produce unique challenges in rehabilitation. A team approach at primary health care level is necessary to diagnose and rehabilitate elderly thereby enabling them to easily lead an independent life.